PELATIHAN INVENTARISASI DIGITAL DATA PERSEDIAAN MELALUI MICROSOFT EXCEL PADA KARYAWAN PONTI DEWATA TEKNIK - Anak Agung Putu Gede Bagus Arie Susandya; I Gede Agus Putra Ardana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Ngurah Rai, 2020)
Inventory plays an important role in the company's operational activities. Inventory management is a must in order to be able to show satisfactory performance. Ponti Dewata Teknik sales process can be said to be less well organized, especially when selling. Because the inventory in Ponti Dewata Teknik does not have computer-based inventory records. So we provide training related to computer-based inventory recording. Where the goal is to facilitate the sales process and increase sales efficiency. Inventory recording with the system can facilitate management in making decisions regarding merchandise purchasing activities. The result of this dedication is that after input through the system, management is able to monitor the increase or decrease in inventory. control of the remaining stock in the warehouse is also effective. Monthly reporting related to inventory also runs effectively and efficiently.